Experimental determination of the statistics of the number of bursts in a cluster of auto-oscillatory systems - Medetov, B.Zh.; Albanbay, N.; Niyazaliyev, K.A. (Recent Contributions to Physics, 2017)
In the study of a cluster of auto-oscillating systems consisting of two coupled FitzHugh-Nagumo neurons, four signal generation modes were defined: "fast", "slow", "bursting", "rest". It is established that the qualitative transition from one regime to another occurs not only in dependence on the given initial conditions and the parameters of the system, but also because of the influence of noise and fluctuations. In addition, it was found that for a certain range of noise intensity for the same parameter values, the number of bursts generated in bursting mode is finite and not constant. To study the regularity of the distribution of the number of bursts, an experimental setup has been assembled, with the help of which the corresponding statistics were measured automatically. The automation of the experiment was carried out by means of LabVIEW, and data processing and calculation of the distribution of the number of bursts were calculated according to a certain algorithm in the Matlab environment. As a result, it is established that the distribution of bursts is described by an exponential dependence.